Gender-equitable Attitudes, Rape Myth Acceptance, and Perceived Peer Acceptance of Violence among High School Students: An Examination of Gender and Athletic Involvement - Bogen, Katherine W. (Journal of interpersonal violence, 2022)
Adolescent relationship abuse (ARA) impacts approximately one-third of teens and is associated with myriad negative health outcomes. Studies on college men indicate that athletes hold less gender-equitable attitudes (GEA), greater rape myth acceptance (RMA), and higher perceived peer support for violence (PSV), and that these attitudes are associated with perpetration risk. However, research has yet to compare the prevalence of these attitudes across gender and athletic status among high school students. The present study addressed this gap by examining the direct and interactive effects of gender and athletic status on GEA, RMA, and PSV in a large sample of high school students living in the United States. Results showed that boys involved in athletics reported lower GEA, higher RMA, and higher PSV than girls involved in athletics and non-athletes. Findings demonstrate the importance of addressing attitudes associated with violent behavior among high school boys involved in athletics, in order to reduce risk of ARA.